2013
DOI: 10.1590/s1516-14392013005000072
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Al-3wt.%Si alloy in unsteady-state horizontal directional solidification

Abstract: The main purpose of this paper is to investigate both the columnar to equiaxed transition and primary dendritic arm spacings of Al-3wt.%Si alloy during the horizontal directional solidification. The transient heat transfer coefficient at the metal-mold interface is calculated based on comparisons between the experimental thermal profiles in castings and the simulations provided by a finite difference heat flow program. Simulated curve of the interfacial heat transfer coefficient was used in another numerical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 39 publications
5
28
0
7
Order By: Relevance
“…Moreover, there will also be a vertical temperature gradient in the sample as soon as a thermosolutal convection roll emerges. In spite of these particular physical characteristics, only a few studies have reported these important effects of melt convection and direction of growth on dendrite arm spacings for this particular case (Carvalho et al 2013, Costa et al 2015, Quaresma et al 2000, Silva et al 2009, 2011.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Moreover, there will also be a vertical temperature gradient in the sample as soon as a thermosolutal convection roll emerges. In spite of these particular physical characteristics, only a few studies have reported these important effects of melt convection and direction of growth on dendrite arm spacings for this particular case (Carvalho et al 2013, Costa et al 2015, Quaresma et al 2000, Silva et al 2009, 2011.…”
Section: Introductionmentioning
confidence: 94%
“…The experimental casting assembly applied to achieve directional solidification of investigated alloys, shown schematically in Figure 1a, was designed at the Federal Institute of Education, Science and Technology of Pará, Brazil, and it was recently published in previous articles (Carvalho et al 2013, Costa et al 2015, Silva et al 2009, 2011. It was manufactured in such a way that the heat was extracted only through the watercooled system placed in the lateral mold wall, promoting horizontal directional solidification.…”
Section: Samples Preparation and Solidificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos recentes têm analisado a significativa influência das condições térmicas envolvidas na transformação líquido/sólido, tais como velocidade de deslocamento da isoterma liquidus (V L ), tempo local de solidificação (t LS ) e taxa de resfriamento (T R ), sobre os aspectos Observa-se que a maioria dos estudos sobre solidificação direcional tem se dedicado a investigar a formação de estruturas dendríticas considerando dispositivos com as configurações verticais ascendente e descendente. Recentemente, pesquisas têm sido conduzidas visando a verificação dos efeitos do vetor gravidade em relação à formação dos espaçamentos dendríticos por meio de experimentos realizados na configuração horizontal (Nogueira et al, 2012;Carvalho et al, 2013;Carvalho et al, 2014). Uma característica interessante do sistema horizontal durante a mudança de fase é o gradiente de concentração de soluto bem como os efeitos de densidade na direção vertical, pois o líquido enriquecido de soluto sempre decanta ao passo que o solvente tende a emergir devido às forças de flutuabilidade.…”
Section: Introductionunclassified
“…Uma característica interessante do sistema horizontal durante a mudança de fase é o gradiente de concentração de soluto bem como os efeitos de densidade na direção vertical, pois o líquido enriquecido de soluto sempre decanta ao passo que o solvente tende a emergir devido às forças de flutuabilidade. Além disso, devido os efeitos impostos pela convecção termossolutal, sempre ocorrerá um gradiente de temperatura na direção vertical (Carvalho et al, 2013;Carvalho et al, 2014). É importante ressaltar que pesquisas relacionadas à evolução microestrutural, utilizando sistemas de solidificação horizontal ainda são bastante raras na literatura (Atwood e Lee, 2003;Voller, 1998;Costa et al, 2015), e destacar a inexistência de correlações entre as variáveis térmicas de solidificação e o comportamento de λ 3 para ligas ternárias nesta configuração.…”
Section: Introductionunclassified